Pembelajaran Matematika Berbasis Unity of Sciences di Sekolah Menengah Atas Berbasis Islam - Nurjanah, Siti; Fitriyah, Aini; Nadhifah, Nadhifah; Nasikhin, Nasikhin (Edumatica : Jurnal Pendidikan Matematika, 2024)
This study aims to analyze the implementation of mathematics learning based on the unity of sciences in Islamic senior high schools. This qualitative research with a case study design collected data through in-depth interviews, observations, surveys, and documentation at MA Yaspia Ngroto Gubug Grobogan. The subjects of this study were five respondents consisting of three grade X students, one grade X mathematics teacher, and one principal. The study results indicate that mathematics learning based on the unity of sciences has significant benefits, such as integrating various disciplines, making learning more relevant and interesting, and creating a dynamic and interactive learning environment. However, several major challenges are faced, including teacher competence, limited resources, less flexible curriculum, and student adaptation to new learning methods. To overcome these challenges, the study found several strategies that can be applied, namely intensive and ongoing training for teachers, provision of adequate resources, development of flexible curriculum, formation of learning communities between teachers of various disciplines, and implementation of teaching strategies that facilitate student transitions. For further research, it is recommended to expand the scope of the study by involving more schools and respondents from various regions. The use of a wider variety of research methods, such as quantitative surveys, classroom observations, and in-depth case studies, can also provide richer and more comprehensive data.